First observation of the competitive double-gamma (γγ/γ) decay process. (June 2016) - Pietralla, N; Walz, C; Scheit, H; Aumann, T; Lefol, R; Ponomarev, V Yu
Abstract: First observation of the competitive double-γ decay process is presented. It is a second-order electromagnetic decay mode. The 662-keV transition from the 11/2 − isomer of 137 Ba to its ground state proceeds at a fraction of 2 x 10 −6 by simultaneous emission of two γ quanta instead of one. The angular correlation and energy distribution of coincident γ quanta are reproduced by a dominant M2-E2 and a minor E3-M1 contribution to the double-γ decay branch. The data are well accounted for by a calculation in the Quasiparticle Phonon Model.